Tech-free activities in your yard - Phillips-Bartlett, Rebecca (Minneapolis, Minnesota Bearport Publishing Company, 2024)
"Put down your device and take a step outside-there's a whole world to explore. It's time to go tech-free in your yard! This fun guide invites young readers to unplug from the world on screens and explore the world around them with easy-to-follow activities for a day in your yard. Spot plants and animals, investigate nature, play games, and more. There's no limit to what you can do when you use a little imagination"--
Includes index.
Ages 6-8
Grades 2-3
113740
Keywords: Outdoor recreation -- Juvenile literature; Outdoor games -- Juvenile literature; Play -- Juvenile literature; Juvenile works